2009
DOI: 10.1051/0004-6361/200911901
|View full text |Cite
|
Sign up to set email alerts
|

Pulsations in the late-type Be star HD 50 209 detected by CoRoT

Abstract: Context. The presence of pulsations in late-type Be stars is still a matter of controversy. It constitutes an important issue to establish the relationship between non-radial pulsations and the mass-loss mechanism in Be stars. Aims. To contribute to this discussion, we analyse the photometric time series of the B8IVe star HD 50 209 observed by the CoRoT mission in the seismology field. Methods. We use standard Fourier techniques and linear and non-linear least squares fitting methods to analyse the CoRoT light… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 22 publications
(35 reference statements)
9
32
0
Order By: Relevance
“…Various causes for what we see in our periodograms can be eliminated: rotational effects on pulsation can be excluded because our periodograms are very different from those of Be stars (e.g. Diago et al 2009). Spots on the surface of the star would give clearly isolated frequencies (and linear combinations between them).…”
Section: Pulsations and Red Noisementioning
confidence: 99%
“…Various causes for what we see in our periodograms can be eliminated: rotational effects on pulsation can be excluded because our periodograms are very different from those of Be stars (e.g. Diago et al 2009). Spots on the surface of the star would give clearly isolated frequencies (and linear combinations between them).…”
Section: Pulsations and Red Noisementioning
confidence: 99%
“…Some others can be identified with the beating frequency of the two stellar frequencies with the highest amplitude or modes with m = 0 (see e.g. Diago et al 2009). Periods that have not been observed during at least 6 cycles (P ≥ T/6) are considered with caution.…”
Section: Long-term Trendmentioning
confidence: 99%
“…The plot shows that, at least at the beginning of the run, the two frequencies exchange their values of power, i.e., the power of F 1 increases when the power of F 2 decreases, and vice versa. Unfortunately, the short duration of the light curve does not allow us to perform a time-frequency analysis, as applied in the study of other Be stars observed during a longer run (see e.g., Diago et al 2009). …”
Section: Analysis Of the Corot Light Curve Of Hd 175869mentioning
confidence: 99%
“…A remarkable finding is the outburst signal detected in the B0.5IVe star HD 49330 (Huat et al 2009), a phenomenon that has not been observed to occur in any of the other observed Be stars, which are of later spectral type. Theoretical work is needed to understand and interpret the observed frequency patterns in the Be pulsators (Neiner et al 2009;Diago et al 2009;Gutiérrez-Soto et al 2009). Progress is hampered by the mathematical complexity of describing the oscillations in these flattened stars, induced by their rapid rotation, often close to their critical velocity.…”
Section: Introductionmentioning
confidence: 99%